PENGARUH GOOD CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP KINERJA PERUSAHAAN - Anisa Mustika Sari; Hiro Tugiman; Annisa Nurbaiti (Jurusan Akuntansi Politeknik Negeri Bandung, 2016)
Abstract: This research aimed to determine the effect of good corporate governance which consisit of bord of commissioner, independent commissioner and audit committee, and size firm, on firm performace measured by Altman Z-Score, either simultaneously or partialliy.This research is descriptive verification and causality research. Unit analysis that used in this research is non manufacturing BUMN. This research using sampel data which chosen through purposive sampling technique and there are 12 firms during six years, from 2010 to 2015. This research using panel data regression analysis technique.The result shows that simultaneously, board of commissioner, independent commissioner, audit committee, and firm size have effect on firm performance. Partially, board of commissioner has positive effect on firm performance. Independent commissioner has no effect on firm performance. Audit committee has positive effect on firm performance, and firm size has no effect on firm performance. Keywords: Good Corporate Governance, Firm Size, Altman Z-Score